2022
DOI: 10.3389/fimmu.2022.959603
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody therapy of herpes simplex virus: An opportunity to decrease congenital and perinatal infections

Abstract: The fetal/neonatal period represents both a unique window of opportunity for interventions as well as vulnerability to a number of viral infections. While Herpesviruses such as herpes simplex virus (HSV) are highly prevalent and typically of little consequence among healthy adults, they are among the most consequential infections of early life. Despite treatment with antiviral drugs, neonatal HSV (nHSV) infections can still result in significant mortality and lifelong neurological morbidity. Fortunately, newbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Other studies have sought to answer this question using polyclonal Ab or monoclonal Abs (mAbs) that could either neutralize or carry out specific effector functions. 10 , 20 While such approaches have contributed to our understanding of the potential contributions of Ab effector functions, disparities in protection from disease could also be attributed to the specific epitope(s) targeted, differences in Ab affinity or avidity, or other factors. Ab Fc engineering strategies that allow separation of Fc-dependent effector functions from neutralization provide a platform to improve experimental resolution in defining Ab-dependent mechanisms of protection, 21 , 22 , 23 , 24 which can inform both vaccine design and therapeutic mAb development.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have sought to answer this question using polyclonal Ab or monoclonal Abs (mAbs) that could either neutralize or carry out specific effector functions. 10 , 20 While such approaches have contributed to our understanding of the potential contributions of Ab effector functions, disparities in protection from disease could also be attributed to the specific epitope(s) targeted, differences in Ab affinity or avidity, or other factors. Ab Fc engineering strategies that allow separation of Fc-dependent effector functions from neutralization provide a platform to improve experimental resolution in defining Ab-dependent mechanisms of protection, 21 , 22 , 23 , 24 which can inform both vaccine design and therapeutic mAb development.…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of ADCC-mediating antibodies were suggested to play an important role for the absent protection by vaccines against HSV-2 [ 47 , 48 ]. The role of antibody-mediated cellular phagocytosis (ADCP) and subsequent immune cell activation in the immune response to HSV-1/2 infection, in particular T-cell activation, has not been investigated in depth [ 47 , 49 ]. ADCP is a known Fc-effector function and has been proposed to be implicated in anti-HSV effects observed in vaccine trials [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…At least 50 mAbs against HSV have been produced and shown to have antiviral effects in vitro and in animal HSV infection models [reviewed in Backes et al ( 37 )]. Three anti-HSV mAbs, 2C (HDIT101), E317 (UB-621) and HSV8, have progressed to human clinical trials ( Table 1B ).…”
Section: Mabs Against Sti Pathogensmentioning
confidence: 99%
“…E317 is an HSV glycoprotein-D specific human IgG1 mAb that can neutralize both HSV-1 and -2. The clinical grade of this mAb, UB-621, was recently determined to be safe and well tolerated in a phase 1 single dose (100 mg/ml) study in healthy volunteers; it is currently being tested in clinical trials for the prevention of orolabial and genital disease ( 37 ) (NCT02346760, NCT03595995, NCT04714060, NCT04979975). HSV8 is a human IgG1 mAb that recognizes HSV glycoprotein-D. A vaginal film, MB66, containing HSV8 and the anti-HIV mAb VRC01, was recently tested in a phase 1 clinical trial; no serious adverse events were reported, and antiviral neutralizing activity (both HIV and HSV) was detected in vaginal secretions from the women up to 24 h after treatment ( 7 ).…”
Section: Mabs Against Sti Pathogensmentioning
confidence: 99%